2011
DOI: 10.5152/akd.2011.031
|View full text |Cite
|
Sign up to set email alerts
|

Circadian blood pressure pattern and cardiac autonomic functions: different aspects of same pathophysiology

Abstract: ÖZETArteriyel kan basıncı sabahın erken saatlerinde zirveye, gece saatlerinde en düşük değerlere ulaşan sirkadiyen bir ritim paterni izlemektedir. Geceleri arteriyel kan basıncındaki düşüş normal sirkadiyen paternin bir parçasıdır. Bu düşüşün görülmediği "non-dipping" olarak adlandırılan sirkadiyen kan basıncı paterni, özellikle hipertansif hastalarda, daha şiddetli hedef organ hasarı ve artmış kardiyovasküler olaylarla birliktedir. Her ne kadar altta yatan mekanizmalar tam olarak bilinmese de "non-dipping" pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…22 Among these factors, growing evidence indicates that nondipping is related to an imbalance between the tone of the sympathetic nerve system and that of the parasympathetic nerve system, particularly the failure to shift from sympathetic to parasympathetic activity during sleep. 19,[23][24][25] In general, plasma and urine catecholamines are lower during the night than they are during the day, 26 and direct recordings from the muscle sympathetic nerves have also shown decreased levels of activity during slow-wave, but not rapid eye movement, sleep. Nocturnal dipping (%): [(daytime SBP -nighttime SBP)/daytime SBP)]*100.…”
Section: Discussionmentioning
confidence: 99%
“…22 Among these factors, growing evidence indicates that nondipping is related to an imbalance between the tone of the sympathetic nerve system and that of the parasympathetic nerve system, particularly the failure to shift from sympathetic to parasympathetic activity during sleep. 19,[23][24][25] In general, plasma and urine catecholamines are lower during the night than they are during the day, 26 and direct recordings from the muscle sympathetic nerves have also shown decreased levels of activity during slow-wave, but not rapid eye movement, sleep. Nocturnal dipping (%): [(daytime SBP -nighttime SBP)/daytime SBP)]*100.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported decreased HRV among hypertensives (31,32). However, limited data exist about HRT in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Hipertansiyon ile yüksek duyarlıklı C-reaktif protein (hs-CRP), KHD ve KHT arasındaki ilişki yaş ve kreatinin seviyesi gibi karıştırıcı değişkenler için düzeltildikten sonra analiz edildi. Bulgular: Sağlıklı gönüllüler ile karşılaştırıldığında, hastaların hs-CRP değerlerinde artış, KHD parametrelerinde hafif, KHT parametrelerinde ise belirgin bozulma tespit edildi [SDNN; 132±28 karşın 112±34 msn, RMSSD;[27][28][29][30][31][32][33][34][35] …”
unclassified
See 1 more Smart Citation
“…3 Nondipper subjects have been reported to have increased cardiovascular morbidity and mortality. [4][5][6] Exercise stress test variables, heart rate recovery (HRR) and chronotropic index (CI), have been shown to have prognostic value. 7 Both an attenuated heart rate (HR) response to exercise (chronotropic incompetence) and HRR after exercise has been considered to reflect cardiac autonomic functions and associated with increased mortality.…”
Section: Cardiac Autonomic Impairment and Chronotropic Incompetence Imentioning
confidence: 99%